Study of Agri-Clinics & Agri-Business Centres for Improving Women Farmers' Access to Extension Services in Agriculture - Nidhi, Rani; Jolly, Masih; Gadhe , Shruthi (Indian Journal of Extension Education, 2017)
Women experience number of constraints to access extension services and other facilities like seed, water, credit,  subsidy etc. The government of India started Agri-Clinics & Agri-Business Centres in 2002 to promote farm  graduates as entrepreneurs in agriculture and allied fields like poultry, fisheries, livestock etc. This study aimed to  ascertain the impact of Agri-Clinics & Agri-Business Centres in 6 states of India namely Punjab, Assam, Tamil Nadu,  Maharashtra, Karnataka and Bihar. Findings indicated that success rate was maximum in Maharashtra followed by  Punjab and Tamil Nadu. Lack of government and bank support could not ensure much success in Bihar while women  graduates evinced keen interest on salaried jobs in Karnataka.
Keywords: Agri-Clinics; Agri-Business Centres; Women; Extension Services